Graduates of Rural Education in Natural Sciences: Socioeconomic profile - Juliano da Silva Martins de Almeida; Wender Faleiro; Welson Barbosa Santos (Universidade Federal do Norte do Tocantins, 2021)
The National Program of Rural Education (Programa Nacional de Educação no Campo - PROCAMPO), initiated in 2012, sought to establish an ensemble of articulated actions in order to improve the quality of education in rural areas of the country by adjusting teacher trainings to such demand. In that context, this paper aims to investigate the socioeconomic profile of graduates in Rural Education with focus on Natural Sciences who got their degrees from UFERSA, UFGD, UFTM and UFFS between 2014 and 2018. The results show that 66.67% of the graduates are female; 57.14% are self-declared Caucasian; aged 32.5 years old, on average; 43% are married; and their average family income is 2 minimum wages (33%). The courses on Rural Education present challenges such as decreasing the dropout/Leave of Absence rates, and guaranteeing that those who were banned from the educational system have the right to continue and finish their higher-education courses. As it is known, the precarization and belittling of the teaching career is generalized in Brazil, but that reality is even more starkly evident in Rural Education.